From nanoparticles to bulk crystalline solid: nucleation, growth kinetics and crystallisation of mixed oxide ZrxTi1−xO2 nanoparticles. Issue 28 (4th July 2017) - Cheng, K.; Chhor, K.; Brinza, O.; Vrel, D.; Kanaev, A.
Abstract : We describe the preparation of mixed metal oxide nanoparticles of a desirable composition and their transformation to the crystalline solids Zr x Ti1− x O2 (0.0 ≤ x ≤ 1.0) after heat treatment. Abstract : We describe the preparation of mixed metal oxide nanoparticles of a desirable composition and their transformation to the crystalline solids Zr x Ti1− x O2 (0.0 ≤ x ≤ 1.0) after heat treatment. The correlation analysis between the size of the nucleus, the crystalline phase and the elemental composition of the solid is presented. Mixed metal oxide zirconium–titanium-oxo-alkoxy (ZTOA) nanoparticles of different elemental compositions 0 ≤ x = C Zr /( C Zr + C Ti ) ≤ 1 were prepared via the sol–gel method in a reactor by rapid micromixing of n -propanol fluids containing the precursors and water. The structural transformation of the nanoparticles takes place in two temperature ranges, 210–250 °C and 380–680 °C, which sensitively depends on the elemental composition. In the range 0.3 ≤ x ≤ 0.6, stable ZTOA nanoparticles with a radius of 2.1 ± 0.05 nm appeared at the hydrolysis ratio H ≤ 1.5. The heat treatment results in a single orthorhombic Zr x Ti1− x O2 phase. The crystallisation onset temperature was the highest in this range of x, attaining 680 °C at x = 0.5. In the range 0 ≤ x ≤ 0.2, the particle radius decreased to 1.6 nm for pure titanium-oxo-alkoxy nuclei (TOA, x = 0); their heat treatment resulted in a single TiO2 anatase phase. In the range 0.7 ≤ x ≤ 1, the particle radius decreased to 1.8 nm for pure zirconium-oxo-alkoxy nuclei (ZOA, x = 1); their heat treatment resulted in mixed monoclinic and tetragonal ZrO2 phases. The crystalline cell parameters of the observed phases underwent a continuous variation with x . TEM images evidenced the nanoporous structure of submicronic orthorhombic Zr x Ti1− x O2 monocrystals with a mean pore size of about that of the ZTOA nanoparticles.